Cutaneous metastasis from gastrointestinal adenocarcinoma of unknown primary origin - Ana Lucia Ariano Junqueira; Ana Maria França Corbett; Jayme de Oliveira Filho; Kassila da Rosa Nasser; Natalie Nejem Haddad; Ana Carolina Franco Tebet (Sociedade Brasileira de Dermatologia, 2015)
AbstractCutaneous metastasis is a rare manifestation of visceral malignancies that indicates primarily advanced disease. Due to its low incidence and similarity to other cutaneous lesions, it is not uncommon to have a delayed diagnosis and a shortened prognosis. We describe the case of a patient who presented with a cutaneous nodule in the sternal region as a first sign of malignancy.